Revised national mathematics curriculum: improving competence in mathematical communication through teaching methods - Pranaitytė, Gabija; Kravčenkienė, Violeta; Narkevičienė, Bronė (Lietuvos matematikos rinkinys, 2023)
The article delves into the topic of mathematical communication development, a key competence outlined in the updated National Mathematics Curriculum. It explores the integration of this competence within the context of the revised curriculum, examining relevant research on mathematical communication and teaching methodologies to foster its growth. Suggestions for pedagogical strategies aimed at enhancing mathematical communication are presented.